The Effectiveness of Schema Therapy on Dysfunctional Attitudes Toward Mate Selection and Emotional Adjustment in Female Students - Silabkhori, Zahra; Kachooei, Mohsen (Advances in Nursing & Midwifery, 2020)
Introduction: Emotional adjustment and people’s attitudes about spouse selection are essential factors that can make a marriage successful or failed. The purpose of this study was to determine the effectiveness of schema therapy on dysfunctional attitudes toward mate selection and emotional adjustment in female students. Methods: The present study was a quasi-experimental study with pretest-posttest design with a control group. Thirty female students were assigned into two experimental and control groups (n = 15 in each group). The experimental group received eight sessions of 90 minutes under schema therapy interventions. For data collection, Attitudes about Romance and Mate Selection Scale (ARMSS) and Emotional Adjustment Measure (EAM) were used. Data were analyzed using an analysis covariance test. Results: Results of covariance analysis showed a significant improvement in the number of dysfunctional attitudes toward the mate selection (P < 0.01) and emotional adjustment (P < 0.01) at the post-test. It can be stated that there are significant changes between the experimental and control groups in the Posttest. Conclusions: Findings showed that schema therapy improves dysfunctional attitudes toward mate selection and emotional adjustment in female students. These interventions can be used to increase people’s preparation to start a marriage and to develop useful attitudes and expectations.